From knowing our needs to enacting change: findings from community consultations with indigenous communities in Bangladesh - Hussain, Sameera; Ruano, Ana Lorena; Rahman, Atiya; Rashid, Sabina Faiz; Hill, Peter S. (International Journal for Equity in Health, 2016)
Includes bibliographical references (page 9-10).